Maturidade pulmonar fetal em gestações complicadas por diabete ou hiperglicemia leve - De Luca, Ana Karina Cristiuma [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O atraso na maturidade bioquímica pulmonar fetal em gestações complicadas por diabete é descrito na literatura, por mecanismos ainda não esclarecidos. Alguns investigadores sugerem que a hiperglicemia e o hiperinsulinismo fetal seriam os responsáveis por essa complicação, pois a quantidade e qualidade do surfactante pulmonar é normal quando o controle glicêmico é adequado. Atualmente, a Síndrome do Desconforto Respiratório (SDR) é complicação rara em recém-nascidos de termo, filhos de mães diabéticas. Mas, ainda há dúvida sobre o comportamento do sistema surfactante nos recém-nascidos, de pré-termo, especialmente, na presença de hiperglicemia não-controlada. Essas observações são também validadas nas gestantes portadoras de hiperglicemia leve, com risco de eventos perinatais adversos, comparável ao das gestantes diabéticas. As secreções do pulmão fetal contribuem na composição do líquido amniótico e a quantidade de surfactante pulmonar pode ser estimada pela medida do surfactante no líquido amniótico. A amniocentese para avaliação da maturidade pulmonar fetal tem sido utiliZada em gestaÇões de risco, inclusive nas complicadas por diabete ou hiperglicemia leve. Em nosso meio, os testes utilizados na avaliação da maturidade pulmonar fetal no líquido amniótico são o Clements, a densidade óptica a 650nm (D065Onm)e a contagem de corpúsculos lamelares (CCL). Avaliar o desempenho de testes de maturidade pulmonar fetal Clements, D0650nme CCL; determinar a influência da qualidade do controle glicêmico matemo nos resultados destes testes, nas gestações complicadas por diabete ou hiperglicemia leve. O projeto foi constituído por dois estudos, um de validação dos testes de maturidade pulmonar fetal e outro de corte transversal, incluindo 192 gestações...

The mechanisms of delayed fetal lung biochemical maturity in pregnancies complicated by diabetes remain elusive. Hyperglycemia and hyperinsulinism have been implicated due to the fact that the quality and quantity of pulmonary surfactant are normal when glycemic control is adequate. At present, Respiratory Distress Syndrome (RDS) is arare' complication in term babies bom to diabetic mothers. However, the behavior of the surfactant system in pre-term babies, especially in the presence of uncontrolled hyperglycemia, is still unclear. These observations are also valid for pregnant women with mild hyperglycemia, whose risk for adverse perinatal events are comparable to that in diabetic pregnant women. The amniotic fluid contains fetal putmonary secretion and the pulmonary surfactant may be quantified by measuring its content in the amniotic fluid. Amnioeentesis has been used to assess fetal lung maturity in risk pregnaneies, including those complicated by diabetes or mild hyperglycemia. Fetal lung maturity in the amniotic fluid is most frequently assessed by the test of Clements, measurernent of aptical density at 650nm (OD650nm)and lamellar body eount (lBC). To evaluate the performance of the test of Clements, optical density at 650nm (OD650nm) and Iamellar body count (lBC) in the assessment of fetallung maturity; to determine the effect of maternal glyeemia control on the results of these tests in pregnancies complicated by diabetes or mild hyperglyeemia. This investigation was divided into two parts: 1) validation of fetal lung maturity tests; 2) Cross-sectional study including 192 pregnancies complicated by diabetes or mild hyperglycemia submitted to fetal lung maturity assessment within at most seven days before delivery and followed up at the Service of Diabetes and Pregnancy of Botucatu Medical Schooll São Paulo State University-UNESP. Exclusion criteria were: amniotic fluid... (Complete abstract click electronic access below)
Keywords: Ammniocentese; Hiperglicemia; Surfactante pulmonar; Diabetes na gravidez; Diabetes and pregnancy